Planejamento estratégico e sua utilização na Cooperativa de Crédito de Livre Admissão São Cristóvão – SICRED São Cristóvão - Mathias, Kelly Guimarães (2011)
This study for the Strategic Planning Credit Union Free Admission St. Kitts which aims to analyze and understand the operational processes for the Strategic and Financial Planning in existing cooperative, define the procedures to be used for the preparation of its planning and after planning as is done to identify and monitor the same and the tools used are efficient and effective managers who need the information. Objective was accomplished through a literature search and was identified with the managers how to develop the strategic planning of the cooperative. In this study there is an evident lack of standardization in strategic planning and cooperative dependence on Excel software for the preparation of financial planning and strategic.